-3-3(-8+5x)=-6(x-5)

Simple and best practice solution for -3-3(-8+5x)=-6(x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3-3(-8+5x)=-6(x-5) equation:


Simplifying
-3 + -3(-8 + 5x) = -6(x + -5)
-3 + (-8 * -3 + 5x * -3) = -6(x + -5)
-3 + (24 + -15x) = -6(x + -5)

Combine like terms: -3 + 24 = 21
21 + -15x = -6(x + -5)

Reorder the terms:
21 + -15x = -6(-5 + x)
21 + -15x = (-5 * -6 + x * -6)
21 + -15x = (30 + -6x)

Solving
21 + -15x = 30 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
21 + -15x + 6x = 30 + -6x + 6x

Combine like terms: -15x + 6x = -9x
21 + -9x = 30 + -6x + 6x

Combine like terms: -6x + 6x = 0
21 + -9x = 30 + 0
21 + -9x = 30

Add '-21' to each side of the equation.
21 + -21 + -9x = 30 + -21

Combine like terms: 21 + -21 = 0
0 + -9x = 30 + -21
-9x = 30 + -21

Combine like terms: 30 + -21 = 9
-9x = 9

Divide each side by '-9'.
x = -1

Simplifying
x = -1

See similar equations:

| 1.9=6.1-0.7x | | 15+5x=x+7 | | (7x-8)+62=180 | | 7/8x-9/8=7 | | 3(4d+1)9d=6(2-d) | | t^2-3/5t+9/100 | | 2/3=4/5-4 | | 8t-5t=-26 | | r=3.7 | | -(1+r)-5=-3r-2 | | 8-((3x-4)/5)=12 | | 48=2l+2(9) | | (8-3x-4)/5=12 | | -4(-4+7p)=-5(5+5p)+8 | | -145=5p | | -16+v=4 | | (8x-3x-4)/5=12 | | 8x-3=5x-45 | | y-2(y-11)=-3(y-2) | | -2(1+7a)=-24+8a | | 36.63=7g+3.59 | | (8x-3-4x)/5=12 | | 160.00+x(0.25)=300.00 | | 11+-5m=-4 | | -2k-7k=9 | | -2k-7k= | | 8x-3-4x/5=12 | | v+(-9)=-8 | | m+5(m-5)=11 | | (6p+54/2)/(6p/6p+54) | | 10+m/6=31 | | 5f+1.1=31 |

Equations solver categories